(E)-2-[(2-Formylphenoxy)methyl]-3-(4-isopropylphenyl)acrylonitrile - V. Manivannan; B. Gunasekaran; M. Bakthadoss; R. Selvakumar; J. Kanchanadevi; G. Anbalagan (Acta Crystallographica Section E, 2013)
In the title compound, C20H19NO2, the dihedral angle between the benzene rings is 77.12 (8)°. The terminal isopropyl group is disordered over two orientations, with site occupancies of 0.720 (14) and 0.280 (14). In the crystal, molecules are linked through a weak C—H...O interaction, forming a zigzag chain along the c-axis direction.